On the Protection of Children's Rights in Côte d'Ivoire: From a Theoretical Perspective to an Effective Law Enforcement - Cissé, Yacouba (Children's Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
In Côte d'Ivoire, the protection of children's rights is governed by a solid legal framework consisting of constitutional provisions, national legislation, and international instruments. This chapter examines the legal regime guaranteeing children's rights, with a focus on constitutional mandates relating to education, health, and protection from exploitation. It explores the implementation of these laws, including mandatory birth registration, parental responsibilities, and the prohibition of child marriage and labor. Despite legislative advances, challenges persist regarding their effective implementation, particularly with regard to statelessness and access to justice. The study highlights the role of national and international monitoring mechanisms in ensuring compliance with child protection standards. By analyzing the theoretical foundations and practical application, this chapter highlights the need to strengthen institutional mechanisms to translate legal provisions into concrete results for children in Côte d'Ivoire.